Fraksi Serat Berbagai Legum Pohon Terpilih sebagai Bahan Pakan Ternak - Rohmiyatul Islamiyati (Universitas Islam Negeri Alauddin Makassar, 2022)
Forage is vital for ruminants. Tree legumes can provide a lifetime food source, supporting the availability of forage for ruminants and green concentrates. The fiber fraction in chemical feed quality testing is more suitable for ruminant feed. This study aimed to analyze the fiber fraction of selected tree legumes. The experimental design used was a Randomized Block Design (RBD) with four treatments of selected tree legume species and three groups as replicates. T1 (Sesbania grandiflora leaves), T2 (Leucaena leucocephala leaves), T3 (Calliandra calothyrsus leaves), and T4 (Moringa oleifera leaves). Data were processed using SPSS version 26 software. A multiple-distance test was conducted to determine if the treatment had a significant effect. The variance results showed that the treatment of selected tree legume species had a significant effect (P<0.05) on the content of NDF, ADF, lignin, hemicellulose, and cellulose. In contrast, insoluble ash had no significant effect (P>0.05). The fiber fraction obtained in this study indicated that the four selected tree legumes had high feed value, good quality and green concentrate source. The lowest lignin content is 2.49% in Moringa leaves.